Tathwir Wasail Ta’lim al-Lughah al-Arabiyah ala Asasi al-Fukahat bi al-Madrasah al-Ibtidaiyah Ma’arif Patihan Wetan Ponorogo / The Development of Comic-Based Arabic Learning Media at Madrasah Ibtidaiyah Ma’arif Patihan Wetan Ponorogo - Muhimmatul Mukaromah; Liza Zubaidah Agustina (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2025)
This research aims to analyze the process of developing Arabic language teaching aids based on humor (KOMIK) at MI Ma’arif Patihan Wetan Ponorogo and to determine its effectiveness. The type of research used is research and development, which refers to the ADDIE model. The data collection method used is observation, interviews, and product validity data analysis using Likert scales and percentage formulas. The results of this research are: 1) The procedures for implementing research and development in this research are as follows: (a) View of the student workbook selected by the school as a learning reference book (b) Knowledge of the content of the material during a semester of learning (c) Understanding the concept of delivering materials in the student workbook (d) Creating a concept similar to the student workbook using the concept of humor (e) Giving humor an attractive appearance (f) Clarifying the purpose of presenting materials in humor (g) Adding some elements to enhance humor. 2) The effectiveness of Arabic language humor for first grade students at MI Ma’arif Patihan Wetan Ponorogo was suitable for use in education. The results of an interview with a fourth-grade teacher at MI Ma’arif Patihan Wetan Ponorogo, revealed that students' grades in Arabic remained relatively unsatisfactory. The current workbooks failed to stimulate students' learning motivation because they provided less interesting material, while learning remained limited due to the lack of adequate facilities to support the learning process. The teacher's efforts aimed to develop learning aids in the form of comics to support teaching and learning activities and make them more enjoyable.المستخلص: أهداف هذه الدراسة لتحليل عملية تطوير وسائل تعليم اللغة العربيّة على أساس الفكاهة  (KOMIK) بالمدرسة الابتدائية معارف فتيهان ويتان فونوروجو ومعرفة فعاليته. نوع البحث المستخدم هو البحث والتطوير، والذي يشير إلى نموذج ADDIE. طريقة جمع البيانات المستخدمة هي الملاحظة والمقابلات وتحليل بيانات صلاحية المنتج باستخدام مقاييس ليكرت وصيغ النسبة المئوية.  نتائج هذه الدراسة هي : 1) أن إجراءات تنفيذ البحث والتطوير وفقًا لـبحثة على الفكاهة التالي:(أ) منظر إلى كتاب أوراق عمل الطالب الذي اختارته المدرسة ككتاب مرجعي للتعلم (ب) معرفة محتوى المادة خلال فصل دراسي من التعلم (ج) فهم مفهوم تسليم المواد في كتاب أوراق عمل الطالب (د) إنشاء مفهوم يشبه كتاب أوراق عمل الطالب باستخدام مفهوم الفكاهة (ه) أعطاء الفكاهة مظهرا جذابا (و) توضيح الغرض من تقديم المواد في الفكاهة (ز) إضافة بعض العناصر لتحسين الفكاهة. 2) كانت فعالية الفكاهة اللغة العربية لطلاب الصف الأول في المدرسة الابتدائية معارف فاتيهان ويتان فونوروجو مناسبة للاستخدام في التعليم. كشفت نتائج مقابلة مع مدرس الصف 4 في مدرسة ابتداءية معارف فتيهان ويتان فونوروجو، أن درجات الطلاب في المواد العربية ظلت غير مرضية نسبيا. لم تتمكن كتاب أوراق عمل الحالية من إثارة دافعية التعلم لدى الطلاب لأنها توفر مواد أقل إثارة للاهتمام، وفي الوقت نفسه لا يزال التعلم محدودًا بسبب توفر المرافق الكافية لدعم عملية التعلم. وكانت الجهود التي بذلها المعلم تهدف إلى تطوير وسائل التعليم على شكل رسوم هزلية لدعم أنشطة التعليم والتعلم وجعلها أكثر ممتعة.